Differentially expressed circular RNAs in a murine asthma model - Bao, Hui (Mol Med Rep, 2020)
Allergic asthma is one of the most common allergic diseases; however, the mechanisms underlying its development have yet to be fully elucidated. Although allergic diseases are inheritable, genetic variance alone cannot explain the notable increase in the prevalence of allergic diseases over a short period of time in recent decades. Recently, research focus has been shifting to epigenetic factors, such as non-coding RNAs. Circular RNAs (circRNAs) are involved in the pathogenesis of various diseases. The aim of the present study was to further elucidate the etiology of allergic asthma by analyzing aberrantly expressed circRNAs in a murine asthma model. A mouse model of house dust mite allergen-induced asthma was established, and the qualified libraries were sequenced using next-generation sequencing. The expression levels of circRNAs were validated by reverse transcription-quantitative PCR (RT-qPCR) analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed for biological pathway classification and enrichment analysis of the aberrantly expressed circRNAs. In addition, the interaction network of the differentially expressed circRNAs and microRNAs (miRNAs) was constructed using Cytoscape. By next-generation sequencing, a total of 150 circRNAs were revealed to be upregulated and 130 were downregulated in the murine asthma model group compared with in the control group. GO and KEGG analyses demonstrated that the differentially expressed circRNAs were mainly involved in processes such as ‘autoimmune disease’, ‘cell adhesion molecules (CAMs)’ and ‘endocytosis’, among others. The expression levels of six circRNAs, namely three upregulated (circ_0000909, circ_0000629 and circ_0000455) and three downregulated (circ_0001454, circ_0000723 and circ_0001389) circRNAs, were validated by RT-qPCR. In conclusion, the analyses suggested that circRNAs performed critical functions via endocytosis (such as macrophage endocytosis), cell adhesion molecules and lipid metabolism in allergic asthma. The interaction network revealed that certain miRNAs that may serve a role in asthma could be regulated by the differentially expressed circRNAs.